Epidemiology of influenza in pregnant women hospitalized with respiratory illness in Moscow, 2012/2013-2015/2016: a hospital-based active surveillance study - Svetlana Trushakova; Lidiya Kisteneva; Beatriz Guglieri-López; Evgenia Mukasheva; Irina Kruzhkova; Ainara Mira-Iglesias; Kirill Krasnoslobodtsev; Ekaterina Morozova; Ludmila Kolobukhina; Joan Puig-Barberà; Elena Burtseva (BMC, 2019)
Abstract Background To better understand the impact of seasonal influenza in pregnant women we analyzed data collected during four seasons at a hospital for acute respiratory infection that specializes in treating pregnant women. Methods This was a single-center active surveillance study of women 15-44 years of age hospitalized for acute respiratory diseases between 2012/2013 and 2015/2016 in Moscow, Russian Federation. Women had to have been hospitalized within 7 days of the onset of symptoms. Swabs were taken within 48 h of admission, and influenza was detected by reverse transcription-polymerase chain reaction. Results During the four seasons, of the 1992 hospitalized women 1748 were pregnant. Laboratory-confirmed influenza was detected more frequently in pregnant women (825/1748; 47.2%) than non-pregnant women (58/244; 23.8%) (OR for influenza = 2.87 [95% CI, 2.10-3.92]; p <  0.001). This pattern was homogenous across seasons (p = 0.112 by test of homogeneity of equal odds). Influenza A(H1N1)pdm09 was the dominant strain in 2012/2013, A(H3N2) in 2013/2014, B/Yamagata lineage and A(H3N2) in 2014/2015, and A(H1N1)pdm09 in 2015/2016. Influenza-positive pregnant admissions went to the hospital sooner than influenza-negative pregnant admissions (p <  0.001). The risk of influenza increased by 2% with each year of age and was higher in women with underlying conditions (OR = 1.52 [95% CI, 1.16 to 1.99]). Pregnant women positive for influenza were homogeneously distributed by trimester (p = 0.37 for homogeneity; p = 0.49 for trend). Frequencies of stillbirth, delivery, preterm delivery, and caesarean delivery did not significantly differ between influenza-positive and influenza-negative hospitalized pregnant women or between subtypes/lineages. Conclusions Pregnant women are at increased risk for hospitalization due to influenza irrespective of season, circulating viruses, or trimester.